2008
DOI: 10.1002/chem.200800117
|View full text |Cite
|
Sign up to set email alerts
|

Highly Phosphorylated Core Oligosaccaride Structures from Cold‐Adapted Psychromonas arctica

Abstract: Many cold habitats contain plenty of microorganisms that represent the most abundant cold-adapted life forms on earth. These organisms have developed a wide range of adaptations that involve the cell wall of the microorganism. In particular, bacteria enhance the synthesis of unsaturated fatty acids of membrane lipids to maintain the membrane fluidity, but very little is known about the adaptational changes in the structure of the lipopolysaccharides (LPSs), the main constituent of the outer leaflet of the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
(79 reference statements)
1
29
0
Order By: Relevance
“…It is widely recognized that cold-adapted bacteria feature modified membrane components to maintain cell membrane fluidity at low temperature through the synthesis of unsaturated fatty acids and by changing the lengths of fatty acids and their degree of phosphorylation [51]. Similarly, it is recognized that membrane sterols are very important components in the regulation of membrane fluidity, permeability, and the activity of membrane bound proteins (e.g., transporters) [52], which are common adaptive mechanisms used by cold-adapted microorganisms [53], [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that cold-adapted bacteria feature modified membrane components to maintain cell membrane fluidity at low temperature through the synthesis of unsaturated fatty acids and by changing the lengths of fatty acids and their degree of phosphorylation [51]. Similarly, it is recognized that membrane sterols are very important components in the regulation of membrane fluidity, permeability, and the activity of membrane bound proteins (e.g., transporters) [52], which are common adaptive mechanisms used by cold-adapted microorganisms [53], [54].…”
Section: Resultsmentioning
confidence: 99%
“…In Gram-negative bacteria, membrane components known as lipooligosaccharides (LOS) have been shown to be important for maintaining membrane fluidity at low temperature [51]. The strain SN2 genome harbors clusters of LOS-like genes for the biosynthesis of capsular exopolysaccharides (AMB_00007130,40,50; AMB_00021260,70,80; AMB_00038110; AMB_00033060,70,80); similar gene clusters were also identified in the genome of the relatively cold-adapted bacterium strain AltDE, while such gene clusters were absent from strain ATCC 27126.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Because microorganisms are at thermal equilibrium with their environment, it is reasonable to assume that structural and functional components in psychrophiles (optimal growth at ≤ 15°C) have adapted, to some degree, to the requirements of a low temperature existence, 4 including the possible presence of ice crystals in their immediate surroundings. The reported mechanisms of bacterial adaptation to low temperature include the over-expression of cold-shock and heat-shock proteins, the presence of unsaturated and branched fatty acids that maintain membrane fluidity, 5 the different phosphorylation of membrane proteins and lipopolysaccharides, [6][7][8][9][10][11] and the production of cold-active enzymes, 12 antifreeze proteins and cryoprotectants. 13 The latter are chemical substances that generally include small molecules, such as glycine betaine, some amino acids, sugars (glucose, fructose) and sugar alcohols (mannitol, glycerol).…”
Section: Introductionmentioning
confidence: 99%
“…All Streptomyces strains used in this study showed better growth in the presence of the polymer. This enhanced growth is probably not the effect of the utilization of suberin constituents as a carbon source (suberin concentration was low), but would rather result from an increase in membrane fluidity that facilitates the transport of nutrients and waste products (5). …”
Section: Discussionmentioning
confidence: 99%